2021
DOI: 10.3892/etm.2021.10321
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 enhances the osteoblastic differentiation of MC3T3‑E1 cells through the Wnt/β‑catenin pathway

Abstract: Leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5) is a Wnt-associated gene that contributes to cell proliferation and self-renewal in various organs. LGR5 is expressed in Ewing sarcoma, and LGR5-overexpressing mesenchymal stem cells promote fracture healing. However, the effects of LGR5 on osteoblastic differentiation remain unclear. The aim of the present study was to explore the function of LGR5 in osteoblastic differentiation. LGR5 was overexpressed or knocked down in the MC3T3-E1 pre-osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Multiple studies have shown that the expression of Wnt6, Wnt10a, and Wnt10b inhibits the differentiation of MSCs into adipocytes while promoting MSCs differentiation into osteoblasts through the canonical Wnt pathway [34]. Furthermore, lots of studies have revealed that Wnt/β-catenin plays an important role in the proliferation and differentiation of embryonic osteoblasts [35,36]. Met also activated the Wnt/βcatenin signaling pathway to reduce inflammation and apoptosis, according to Zhang et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that the expression of Wnt6, Wnt10a, and Wnt10b inhibits the differentiation of MSCs into adipocytes while promoting MSCs differentiation into osteoblasts through the canonical Wnt pathway [34]. Furthermore, lots of studies have revealed that Wnt/β-catenin plays an important role in the proliferation and differentiation of embryonic osteoblasts [35,36]. Met also activated the Wnt/βcatenin signaling pathway to reduce inflammation and apoptosis, according to Zhang et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [38] also found that NMN relieved senescence in osteoblasts and improved bone repair in osteoporotic mice. The Wnt/β-catenin signaling pathway has been shown to stimulate bone formation and remodeling during osteogenesis [29], and various studies have demonstrated that osteogenic differentiation was induced in MC3T3-E1 cells via the Wnt/β-catenin signaling pathway [33,39,40]. However, to date, no research has clarified whether NMN can ameliorate LPS-induced impairment of osteogenesis or if NMN's influence on osteogenesis is mediated by the Wnt/ β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…BMP-2 played a key role in bone regeneration. Studies have proven that overexpression of leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5) can activate the Wnt/β-catenin pathway and thereby enhance the osteogenic differentiation of MC3T3-E1 cells . The study of Li et al suggested that MFAP5 could regulate the osteogenic differentiation of BMSCs through the Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proven that overexpression of leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5) can activate the Wnt/β-catenin pathway and thereby enhance the osteogenic differentiation of MC3T3-E1 cells. 50 The study of Li et al 51 suggested that MFAP5 could regulate the osteogenic differentiation of BMSCs through the Wnt/β-catenin signaling pathway. It was claimed by Yang et al 52 that amyloid β peptide (Aβ) enhanced the osteogenic differentiation of human BMSCs and upregulated the expression of RUNX2 and OC through the Wnt/ β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%